Studi Kelayakan Teknis Potensi Energi Terbarukan Mini Hydro Di Desa Goal Kecamatan Sahu Timur Kabupaten Halmahera Barat - Nurharyanto, Riyan Tri; Gunawan, Iwan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
The government has committed to achieving carbon neutrality by 2060 or earlier, with one of the steps to reduce emissions being the endorsement of PT Perusahaan Listrik Negara's General Plan for Electricity Supply (RUPTL) 2021-2030. The RUPTL stipulates that more than half, 51.6% or equivalent to 20.9 Giga Watt (GW), will come from renewable energy sources rather than fossil fuels. The potential of renewable energy, such as mini hydro power plants, is the focus of this effort. Indonesia has great potential in New Renewable Energy (NRE), including 450 MW of mini/micro hydro, with North Maluku alone having a possibility of 145.1 MW. One of the strategic issues at the national level is energy security, particularly in the North Maluku River Basin. The North Halmahera River Basin, which covers West Halmahera Regency, North Halmahera Regency, and Morotai Island Regency, is the primary focus in exploring the potential of micro hydropower plants. To fully utilise the potential of renewable energy and address the strategic issue of energy security, research needs to be conducted on the planning of MHP in Goal Village, with a case study on Akelamo River. The results of the research and analysis show that the water discharge reaches 7.86 m3/det with a head of 16 metres. The potential power that can be generated using Kaplan turbines is 817.21 kW. These steps can serve as a foundation for implementing sustainable MHP development projects. They can contribute significantly to the achievement of net zero emission targets that the government has promised.